1979
DOI: 10.1515/cclm.1979.17.8.553
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 9 Methods for the Determination of Cholesterol

Abstract: Summary: Seven enzymatic procedures for the determination of cholesterol in serum were compared with the Liebermann-Burchard-and a gas-chromatographic method. Using a decision matrix all methods could be ranked according to reliability and practicability. With the exception of the cholesterol oxidase-coupled Kageyama principle and the Liebermann-Burchard procedure, all the other methods showed similar reliability. Vergleich von 9 Methoden zur Bestimmung von CholesterinZusammenfassung: Sieben enzymatische Verfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
5
0
2

Year Published

1980
1980
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 17 publications
0
5
0
2
Order By: Relevance
“…Recently it was demonstrated that the enzymatic reactions for the determination of cholesterol concentrations proceed via more complicated pathways than was previously expected (11,13,(16)(17)(18)(19).…”
mentioning
confidence: 92%
See 2 more Smart Citations
“…Recently it was demonstrated that the enzymatic reactions for the determination of cholesterol concentrations proceed via more complicated pathways than was previously expected (11,13,(16)(17)(18)(19).…”
mentioning
confidence: 92%
“…The cholesterol concentrations obtained with the enzymatic method are usually lower than those obtained by the Liebermann-Burchard method (5,7,11,13). This was explained by the higher specificity of the enzymatic methods.…”
mentioning
confidence: 98%
See 1 more Smart Citation
“…aber neben dem unangenehmen Umgang mit den sehr *"eungen zu überprüfen. aggressiven Reagenzien haftet der Methode der Nachteil der Bei diesem neu entwickelten Test (9) (10,11). Die Medikamente wurden jeweils in hoher Dosierung (i.a.…”
Section: Introductionunclassified
“…Eine mögliche Störung durch Arzneimittel wurde für die sog. Dies führt nach den Untersuchungen von Haeckel et al(16) jedoch nicht zu einer höheren Arzneimittelinterferenz. Bei Übertragung dieser Ergebnisse auf das hier beschriebene Verfahren muß die geringere Spezifität der Peroxidäse-Methode beachtet werden.…”
unclassified